Fenomena Al-Dakhil Dalam Tafsir Lughawi: (Menelisik Kajian Linguistik Dalam Tafsir Al-Kashaf Karya Al-Zamakhshari) - Ahmad Sahal Aqil Abrori, Aqil; Meirando Rukhuz (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Theological aspects are significant in influencing the paradigm of an interpreter's interpretation, and Zamaksyari as a Mu'tazilah also has a theological tendency that influences his interpretation and this is called al-dakhil. So this article wants to further analyze the infiltration in the interpretation of al-Kashaf in its linguistic aspects. Therefore, this article is a qualitative-based research that uses content analysis with the theory of al-Dakhil and this article emphasizes the linguistic approach. Linguistic rules are used to explain the meanings of the Qur'an. In this study, it was found in the interpretation of al-Zamaksharī which is included in al-Dakhil although not entirely but some of his interpretations reflect the school of thought he adheres to. This is inseparable from the background of al-Zamakhsharī's subjectivity as a theologian of the Mu'tazilah school.